Penerapan Statistical Quality Control Menggunakan U-Chart, Demerit Chart, dan EWMA pada Proses Produksi Manufaktur - Hilda Umayyah Anak Ampun; Unedo Nainggolan; Valtino Gabriel Gultom (Codeverse: Journal of Emerging Digital Realities, 2025)
Quality control is a crucial aspect in the manufacturing industry to ensure product consistency and minimize defects that may affect production efficiency and customer satisfaction. This study aims to analyze quality control in a manufacturing process using the Statistical Quality Control (SQC) approach. The methods applied include the U-Chart to monitor defects per unit, the Demerit Chart to evaluate defect severity, and the Exponentially Weighted Moving Average (EWMA) to detect small process shifts. The data used are secondary data consisting of production quantity, number of defects, and types of defects over 28 observation periods. The results show that the U-Chart and Demerit Chart indicate the process is statistically in control, although some points approach control limits. In contrast, the EWMA method identifies points outside the control limits, suggesting the process is not fully stable. Therefore, continuous monitoring is required to improve quality and maintain process stability.